Analisis Karakteristik Material Camshaft AISI 8620 dan Besi Cor Kelabu menggunakan Metode Metalografi dan Spektrometri Optik - Setijo Budi, Sigit; Hendrawan, Andre Budhi; Akhmadi, Amin Nur; Nashrudin, Hafidz (CV. IRA PUBLISHING, 2025)
The demand for non-OEM camshafts is increasing, but this raises concerns about material quality. This study analyses the material characteristics of AISI 8620 and grey cast iron camshafts used in 125cc automatic motorcycles. Testing was conducted using Metallography and Optical Emission Spectrometry. AISI 8620 exhibits a fine ferrite-pearlite microstructure and alloying elements such as chromium and molybdenum, which support heat treatment. Cast iron exhibits a pearlite structure with flake graphite, providing superior damping but less toughness. The results indicate that AISI 8620 is more suitable for high-load applications, while cast iron is suitable for lightweight and cost-effective applications. This study provides important insights into material selection for motorcycle camshaft manufacturing.